CORRELATION BETWEEN END-TIDAL CO2 AND ABGS PaCO2 IN NEONATES ON MECHANICAL VENTILATION - ISHAQ , M; ULLAH , R; BIBI , M; ULLAH , K (Biological and Clinical Sciences Research Journal, 2023)
Monitoring arterial blood gases (ABGs) is essential for neonates requiring mechanical ventilation. End-tidal CO2 (EtCO2) emerges as a promising alternative for long-term monitoring due to its less intrusive and faster measurement. However, the relationship between EtCO2 and ABGs PaCO2 in mechanically ventilated neonates remains unclear. This study aims to ascertain the reliability of EtCO2 as a surrogate marker for ABGs PaCO2 in neonates on mechanical ventilation at Combine Military Hospital (CMH) Rawalpindi. This prospective observational study was conducted at CMH Rawalpindi between October 15, 2022, and July 15, 2023. The study included 100 neonates in the CMH Rawalpindi Neonatal Intensive Care Unit (NICU) requiring mechanical ventilation within the first 28 days of life. ABG blood samples were collected at predefined intervals, and capnography assessed EtCO2. The association between ABGs PaCO2 and EtCO2 was evaluated using Pearson's correlation coefficient. The study cohort comprised 52 male and 48 female neonates with an average age of 4.7 days, all undergoing mechanical ventilation. ABGs and EtCO2 were monitored for up to 24 hours, revealing a significant positive association between ABGs PaCO2 and EtCO2 (P < 0.01, Pearson's correlation value = 0.82). The Bland-Altman plot indicated a mean bias of -2.3 mmHg with limits of agreement from -8.1 to 3.5. The association remained consistent across age, sex, and respiratory distress severity. In neonates receiving mechanical ventilation at CMH Rawalpindi, EtCO2 and ABGs PaCO2 exhibit a positive correlation. EtCO2 emerges as a potentially reliable option for quick and less invasive monitoring of PaCO2 levels in this population.